Colonic Necrosis in a 4-Year-Old with Hyperlipidemic Acute Pancreatitis - Tiffany J. Patton; Timothy A. Sentongo; Grace Z. Mak; Stacy A. Kahn (Hindawi Limited, 2016)
Here we report the case of a 4-year-old male with severe acute pancreatitis due to hyperlipidemia, who presented with abdominal pain, metabolic abnormalities, and colonic necrosis. This colonic complication was secondary to the extension of a large peripancreatic fluid collection causing direct serosal autodigestion by pancreatic enzymes. Two weeks following the initial presentation, the peripancreatic fluid collection developed into a mature pancreatic pseudocyst, which was percutaneously drained. To our knowledge, this is the youngest documented pediatric case of colonic necrosis due to severe pancreatitis and the first descriptive pediatric case of a colonic complication due to hyperlipidemia-induced acute pancreatitis.